Formation of Fiber Materials by Pneumatic Spraying of Polymers in Viscous-Flow States; Russian Physics Journal; Vol. 59, iss. 10 - Lysak I. A. Ilya Aleksandrovich; Malinovskaya T. D. Tatjyana Dmitrievna; Lysak G. V. Galina Vladilenovna; Potekaev A. I. Aleksandr Ivanovich; Kulagina V. V. Valentina Vasiljevna; Tazin D. I. Dmitry Ivanovich (2017, 2017)
Title screen